Answer:
x=0, y=-2
Step-by-step explanation:
Given equations are:
\[-3x-y=2\] ---- (1)
\[x-y=2\] ---- (2)
Subtracting equation 1 from equation 2:
\[(x-y)-(-3x-y) = 2-2\]
\[x-(-3x) = 2-2\]
=> \[x+ 3x = 0\]
=> \[4x = 0\]
=> \[x= 0/4\]
=> \[x=0\]
Substituting the value of x=0 in equation 2:
\[0-y=2\]
=> \[y= -2\]
So the solutions of the given equations by elimination are : x=0, y=-2
Validating the solution by substituting in equation 1:
Left Hand Side : \[-3 * 0 - (-2) = 0 +2 = 2\]
Right Hand Side : 2
Since the two sides are equal, the solution is valid.